Reproduction of Artibeus lituratus and Sturnira lilium (Chiroptera: Phyllostomidae) in a Semideciduous Seasonal Forest fragment in southern Brazil - Rocha Ribas, Mateus; Batista, Sara Cristina; Kramer, Jean Freitag; Aranha, José Marcelo Rocha (Acta Biológica Paranaense, 2022)
Here we evaluate the reproduction and changes in abundance among different reproductive stages for Artibeus lituratus (Olfers, 1818) and Sturnira lilium (E. Geoffroy, 1810) in a Semideciduous Seasonal Forest fragment at southern Brazil. Bats were identified according with sex and reproductive stages based on secondary characters, as follows: young bats (1); males with descending testes (2); males with abdominal testes (3); non-pregnant females (4); lactating females (5); pregnant females (6); pregnant-lactating females (7); post-lactation females (8). Abundance was explored monthly in each reproductive stage considering rainy (October to March) and dry (April to September) season. Bat abundance changed over the months and between species, with August and June with highest abundance for A. lituratus and February, June and September for S. lilium. Both species showed a pattern of bimodal polyestry, with first pregnancy occurring at the end of dry season and second in the middle of rainy season. The data here presented contribute to understand reproductive biology and abundance changes over one year for A. lituratus and S. lilium in a Semideciduous Seasonal Forest fragment, reducing knowledge gap about reproduction patterns of these species.